Photodetectors: Inorganic UV–Visible–SWIR Broadband Photodetector Based on Monodisperse PbS Nanocrystals (Small 10/2016). Issue 10 (7th March 2016) - Lee, Jae Woong; Kim, Do Young; Baek, Sujin; Yu, Hyeonggeun; So, Franky
Abstract : Synthesis of highly mono‐dispersed large PbS nanocrystals (NCs) with low particle size dispersion is demonstrated by F. So and co‐workers on page 1328, by controlling the sulfur concentration below the nucleation threshold during multiple injections of the sulfur precursor. These NCs are used to fabricate multi‐spectral photodetectors and high detectivity values in the UV‐Visible‐SWIR (short‐wave‐IR) wavelength range from 350 nm to 2000 nm are demonstrated.